Numerical simulation of flattened heat pipe with double heat sources for CPU and GPU cooling application in laptop computers. Issue 2 (26th December 2020) - Sanhan, Wisoot; Vafai, Kambiz; Kammuang-Lue, Niti; Terdtoon, Pradit; Sakulchangsatjatai, Phrut
Abstract: An investigation of the effect of the thermal performance of the flattened heat pipe on its double heat sources acting as central processing unit and graphics processing unit in laptop computers is presented in this work. A finite element method is used for predicting the flattening effect of the heat pipe. The cylindrical heat pipe with a diameter of 6 mm and the total length of 200 mm is flattened into three final thicknesses of 2, 3, and 4 mm. The heat pipe is placed under a horizontal configuration and heated with heater 1 and heater 2, 40 W in combination. The numerical model shows good agreement compared with the experimental data with the standard deviation of 1.85%. The results also show that flattening the cylindrical heat pipe to 66.7 and 41.7% of its original diameter could reduce its normalized thermal resistance by 5.2%. The optimized final thickness or the best design final thickness for the heat pipe is found to be 2.5 mm. Graphical Abstract: